A prospective parallel design study testing non-inferiority of customized oral stents made using 3D printing or manually fabricated methods. (July 2020) - Zaid, Mohamed; Koay, Eugene J.; Bajaj, Nimit; Mathew, Ryan; Xiao, Lianchun; Agrawal, Anshuman; Fernandes, Pearl; Burrows, Hannah; Roach, Millicent A.; Wilke, Christopher T.; Chung, Caroline; Fuller, Clifton D.; et al.
Highlights: Prospectively evaluated customized 3D printed stents compared to standard stents. 3D printed stents demonstrated non-inferior patient reported outcomes. 3D printed stents achieved similar and reproducible intraoral positioning. 3D printed stents have low production cost, and short fabrication time. 3D printed stents can be widely utilized in any radiation oncology practice. Abstract: Background and purpose: Customized mouth-opening-tongue-depressing-stents (MOTDs) may reduce toxicity in patients with head and neck cancers (HNC) receiving radiotherapy (RT). However, making MOTDs requires substantial resources, which limits their utilization. Previously, we described a workflow for fabricating customized 3D-printed MOTDs. This study reports the results of a prospective trial testing the non-inferiority of 3D-printed to standard and commercially-available (TruGuard) MOTDs as measured by patient reported outcomes (PROs). Materials and methods: PROs were collected at 3 time points: (t1) simulation, (t2) prior to RT, (t3) between fractions 15–25 of RT. Study participants received a 3D-printed MOTDs (t1, t2, t3), a wax-pattern (t1), an acrylic-MOTDs (t2, t3) and an optional TruGuard (t1, t2, t3). Patients inserted the stents for 5–10 min and completed a PRO-questionnaire covering ease-of-insertion and removal, gagging, jaw-pain, roughness and stability. Inter-incisal opening and tongue-displacement were recorded. With 39 patients, we estimated 90% power to detect a non-inferiority margin of 2 at a significance level of 0.025. Matched pairs and t -test were used for statistics. Results: 41 patients were evaluable. The 3D-printed MOTDs achieved a significantly better overall PRO score compared to the wax-stent (p = 0.0007) and standard-stent (p = 0.0002), but was not significantly different from the TruGuard (p = 0.41). There was no difference between 3D-printed and standard MOTDs in terms of inter-incisal opening (p = 0.4) and position reproducibility (p = 0.98). The average 3D-printed MOTDs turn-around time was 8 vs 48 h for the standard-stent. Conclusions: 3D-printed stents demonstrated non-inferior PROs compared to TruGuard and standard-stents. Our 3D-printing process may expand utilization of MOTDs.